UPAYA MEKSIKO DAN AMERIKA SERIKAT DALAM MENGATASI EKSISTENSI DTO (DRUGS TRADE ORGANIZATION) KAWASAN MEKSIKO - Delfira Harli Saputri; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research was written with the aim of describing what efforts were made by Mexico and the United States in tackling drug trafficking by Mexican cartels or commonly known as DTOs. The existence of Mexico's DTO in the United States has disrupted the security of the two countries to the point where it affects many sectors. What was done by the DTO is categorized as a transnational crime. In responding to these conditions, Mexico and the United States need to take repressive measures to control drug trafficking that occurs. The method used in this study is a qualitative method that is explanatory and uses the theory of Securitization by Barry Buzan. Security is the most important factor for the sovereignty of a country. This is a problem for Mexico and the United States over their concern for the Mexican DTO which carries out its activities in the border area between the two countries. The efforts made by Mexico and the United States took the form of an international treaty policy known as the Merida Initiative. The Merida Initiative collaboration is driven by domestic and international factors related to the impacts caused by drug trafficking in the territories of the two countries. Keywords: DTO, Merida Initiative, Drugs Trafficking, Transnational Crime.